THE EFFECT OF OPERATING CASH FLOW AND NET PROFIT ON SHARE RETURN, 2022-2022 - Abdul Karim (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out, analyze and describe the effect of operating cash flow and net income on stock returns in 2022-2022 in agricultural sector companies. This study uses secondary data contained in the Indonesian Stock Exchange. With the sample technique carried out by the author, the authors obtained a sample of this research as many as 7 companies from 21 companies in the agricultural sector, from 2022-2022 with annual data from operating cash flow and net income on stock returns resulting in 32 data in this study.